Molecular Identification and Determination of Some Virulence Genes of Aeromonas Spp. in Fish and Water From Turkish Coastal Regions - Onuk, E.E.; Findik, A.; Türk, N.; Altun, S.; Korun, J.; Özer, S.; Avsever, M.L. (Ecole Nationale Veterinaire Toulouse, 2013)
Identification of Aeromonas species is known to be troublesome due to their phenotypic and genotypic heterogeneity. A total of 60 bacterial isolates from water and rainbow trout samples from Turkish coastal regions (Black Sea, Aegean Sea and Mediterranean Sea) were used for 16S rDNA-Restriction Fragment Length Polymorphisms (RFLP) analysis with AluI, MboI, NarI and PstI as restriction enzymes and molecular identification was eventually completed with PCR amplification of the fstA, A. salmonicida specific gene. In addition, the presence of 6 virulence genes (aer, ser, lip, gcat, nuc and laf) in the isolates was investigated using rapid hexaplex-PCR. The frequencies of the identified Aeromonas species were 38.33% for A. sobria, 23.33% for A. hydrophila, 10.0% for A. veronii and 26.67% for A. salmonicida and only one strain was not clearly identified. The more frequent virulence genes were aer, ser, lip and gcat found in 66.66%, 61.67%, 50% and 33.33% of isolates, respectively and 14 different virulence profiles were determined. This study shows that the 16S rDNA RFLP analysis combined with fstA gene specific PCR was useful for rapid and reliable identification of Aeromonas strains and the coupled determination of the virulence genes may help to both control fish disease arising from Aeromonas spp. and alert human health risk.
Keywords: Aeromonas; Fish; Restriction Enzymes; RFLP; Turkish Coastal Regions; Virulence Genes